Interrogating Governance and Constitutional Issues of Local Government System in Nigeria - Diekola, Oluseyi J.; Shiyanbade, Bolanle W.; Adeyeni, Olusegun B.; Wahab, Yusuf B.; Ambali, Sodiq A. (African Journal of Stability and Development (AJSD), 2019)
The Constitution of the Federal Republic of Nigeria 1999, as amended, contains some provisions for the creation of local government as the third tier of government whose objective is to ensure effective, measurable and efficient service delivery to the people, while bringing government closer to people at the rural communities in order to attain the transformation of lives in these communities. However, local governments in Nigeria are facing various difficulties which have brought to the fore the question of local government autonomy. The experience with many Local Government Areas is that their states starve them of the statutory grants, and in the process deny them the opportunity of rendering essential services as required. The major concern of this paper is identifying these difficulties and the factors responsible for them. In achieving this, the paper relies on descriptive approach. The conclusion of the paper is that problems confronting local governments in Nigeria are multifarious, and the solutions for them should be adequate and practical to evolve into a viable and development-oriented third tier of government.